Identifikasi Senyawa Metabolit Sekunder Ekstrak Etanol Cangkang Sacha Inchi (Plukenetia volubilis L.) - Astria Endesei; Yuszda K. Salimi; Netty Ino Ischak; Ahmad Kadir Kilo; Hendri Iyabu; La Ode Aman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aimed to identify the secondary metabolite compounds present in the ethanol extract of Plukenetia volubilis L. (sacha inchi) shells through phytochemical screening and LC-MS analysis. The extraction was performed using the maceration method with 95% ethanol as solvent, resulting in a yield of 47.33%. Qualitative phytochemical tests revealed the presence of alkaloids, flavonoids, tannins, terpenoids, saponins, and glycosides in the extract. Further LC-MS analysis tentatively identified several phenolic and flavonoid compounds with known biological activities, including sinapinic acid, 1-o-sinapoylglucose, and azelaic acid from the dicarboxylic acid group. The presence of these compounds highlights the potential of sacha inchi shell extract as a natural antioxidant and antidiabetic agent. These findings support the valorization of sacha inchi agricultural waste as a promising raw material for pharmaceutical and nutraceutical applications.